A case of median sacral artery avulsion injury by L4–5 lateral dislocation fracture. (June 2021) - Nagasawa, Hiroki; Omori, Kazuhiko; Yanagawa, Youichi
Abstract: Introduction: The median sacral artery injury is a rare entity, especially in trauma. And the injuries are always with pelvic fractures. We describe a case of the median sacral injury which was induced by blunt trauma without pelvic fractures. Case presentation: A 26-year-old male who suffered L4–5 fracture dislocation and some hemorrhage in pelvic cavity following a motorcycle accident. He had a median sacral artery injury, and we tried to the trans-catheter arterial embolization, however it could not be success. The embolization was performed using of gelatin sponges in bilateral internal iliac artery and left 4th lumber artery. After his admission, a demand of transfusions lasted for 7 days. Conclusion: We successfully treated a case of median sacral avulsion injury by choosing conservative treatment.